Восстание 1916 года в низовьях амударьи: Взгляд через столетие - Utegenov Khakimbay Maksetovich (International Journal of Advanced Science and Technology, 2020)
This article analyses the reasons and the process of the uprising in Khiva Khanate and the part of Amudarya in 1916. The author puts forward a new approach for leaning this event in antiquity. Also, this article shows the degrees of achievements of Historian Scientists.